Od "Carmina" III 16 Horacego do "Przeważnej legacyji" Samuela Twardowskiego. Między liryką a epiką - Kuran, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
This text presents relations between Horacy’s Carmina III 16 and two short parts The important Mission of His Grace Duke Krzysztof Zbaraski Samuel from Skrzypna Twardowski. Author tries to present the role of the lyric text in the long epic story. Very important is a role of Jan Kochanowski’s Song II 4. He unites mythological and Horatian themes Danae and gold. In the Iwardowski’s text exists myth in the Kochanowski’s version. Twardowski alludes to situation at the Turkey’s court and emperors love of gold, because he describes duke’s visit, presents dangerous situation of legate and behaviour of Turkey ruler. In The important Mission author carries on an intertekstual game with the reader, he directs him to mythological, Horatian and Kochanowski’s texts. He is going to presents behaviour type of ruler.